Impact of Werther Effect Exerted by Social Media on Individuals Presenting with Deliberate Self-Harm (DSH) to a Tertiary Care Hospital in Sri Lanka - Isuri Wimalasiri; Aindralal Balasuriya; Madhubhashini Dayabandara (BJPsych Open)
Aims: There was an exponential increase in the rates of deliberate self-harm (DSH) in Sri Lanka over the last two decades coinciding with the rise of social media. Werther effect is the phenomenon where sensationalised media reports on suicide/DSH leads to increased rates of DSH/suicide. Therefore, assessing the impact of social media on DSH and implementing media regulations are timely needs. The objectives of this study included assessing the extent of exposure and the severity of emotional disturbance incurred due to social media content depicting DSH/suicide and determining the association between exposure and emulating DSH behaviour they were exposed to.